2022
DOI: 10.3389/feduc.2022.765233
|View full text |Cite
|
Sign up to set email alerts
|

Research on Technological Pedagogical and Content Knowledge: A Bibliometric Analysis From 2011 to 2020

Abstract: This study was to explore the bibliometric characteristics of TPACK from 2011 to 2020. By using the keyword “TPACK,” the bibliographic references have been retrieved from the Scopus databases (date of search: March 7, 2021). The VOSviewr software tool and Bibliometrix R package were used for information analysis. The results confirmed that there are 700 articles, representing 63 countries and 159 journals scanned. Articles in 2013 were cited the most times, and since 2016, the number of articles is on the rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 55 publications
(67 reference statements)
2
21
0
3
Order By: Relevance
“…Recently, more and more literature reviews on TPACK have been published (e.g., Wang et al, 2018;Yeh et al, 2021;Tseng et al, 2022). This trend is consistent with findings reported by Lee et al (2022).…”
Section: Discussionsupporting
confidence: 87%
“…Recently, more and more literature reviews on TPACK have been published (e.g., Wang et al, 2018;Yeh et al, 2021;Tseng et al, 2022). This trend is consistent with findings reported by Lee et al (2022).…”
Section: Discussionsupporting
confidence: 87%
“…As a result, presenting an overview of current research output in science education within TPACK framework field has become an important task. To best of my knowledge, bibliometric analysis of TPACK literature is not limited to science education field, but it involve multidisciplinary field (e.g Ye, Chen, & Kong, 2019;Soler-Costa et al, 2021;Lee, Chung, & Wei, 2022;Zou et al, 2022). This prompted us to perform a bibliometric analysis in order to create the summary of the current state of the literature in the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…Several such studies have pointed out that there are articles where these two concepts co-exist. In other words, in studies around TPACK, the concept of STEAM was observed and vice versa (Aguilera & Ortiz-Revilla, 2021;Irwanto, 2021;Kutluca & Merkan, 2022;Lee et al, 2022;Porras et al, 2022;Putri et al, 2022). However, there seems to be a limited number of bibliometric studies that specifically aim to determine whether there are articles that study both of these terms.…”
Section: Methodsmentioning
confidence: 99%
“…Simultaneously, Lee et al (2022) carried out a bibliometric study on 700 publications, disseminated between 2011 and 2020, in an effort to achieve science mapping. They also concluded that there is an increased emphasis on TPCK.…”
Section: Technological Pedagogical Content Knowledgementioning
confidence: 99%